2020
DOI: 10.1017/s030500092000032x
|View full text |Cite
|
Sign up to set email alerts
|

Scalar and ad-hoc pragmatic inferences in children: guess which one is easier

Abstract: Several studies investigated preschoolers’ ability to compute scalar and ad-hoc implicatures, but only one compared children's performance with both kinds of implicature with the same task, a picture selection task. In Experiment 1 (N = 58, age: 4;2-6;0), we first show that the truth value judgment task, traditionally employed to investigate children's pragmatic ability, prompts a rate of pragmatic responses comparable to the picture selection task. In Experiment 2 (N = 141, age: 3;8-9;2) we used the picture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
5
18
1
Order By: Relevance
“…The studies to-date suggest that young children often fail at restricting the meaning of scalar quantifiers through pragmatic strengthening, but succeed at doing so with numerals (Huang et al, 2013;Panizza et al, 2013), ad hoc implicatures (Stiller et al, 2015;Foppolo et al, 2020) whilst also mastering their understanding and use of the principle of contrast, another kind of pragmatic inferencing, to acquire new words. Furthermore, given that 3-year-old children are competent in other tasks requiring sophisticated pragmatic skills like theory of Mind (Onishi and Baillargeon, 2005), counterfactual thinking (Harris et al, 1996) it would only be reasonable to expect that they ought to be able to generate scalar implicatures with similar ease.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The studies to-date suggest that young children often fail at restricting the meaning of scalar quantifiers through pragmatic strengthening, but succeed at doing so with numerals (Huang et al, 2013;Panizza et al, 2013), ad hoc implicatures (Stiller et al, 2015;Foppolo et al, 2020) whilst also mastering their understanding and use of the principle of contrast, another kind of pragmatic inferencing, to acquire new words. Furthermore, given that 3-year-old children are competent in other tasks requiring sophisticated pragmatic skills like theory of Mind (Onishi and Baillargeon, 2005), counterfactual thinking (Harris et al, 1996) it would only be reasonable to expect that they ought to be able to generate scalar implicatures with similar ease.…”
Section: The Present Studymentioning
confidence: 99%
“…Theory of Mind in development, Csibra and Gergely, 2009;Rhodes and Brandone, 2014), (b) restrict the meaning of unknown words given their knowledge of other familiar words (cf. Principle of Contrast Clark, 1990;Halberda, 2003) and (c) adopt pragmatic strengthening in other dimensions such as numerals (Panizza et al, 2013) and ad hoc scales (Stiller et al, 2015;Foppolo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even stronger evidence for the existence of an association between ToM and SIs in language acquisition comes from the recent study of Foppolo et al (2020). Importantly, this study was the first to systematically assess in monolingual TD children the possible correlations between SI generation, on one hand, and linguistic and cognitive abilities (lexical and morphosyntactic comprehension, IQ, and first-order ToM), on the other.…”
Section: Scalar Implicature Generation and Tommentioning
confidence: 95%
“…The lexical alternatives account has found support from studies showing that while children are impaired on scalar implicatures, they derive ad hoc implicatures based on the same materials with ease (Horowitz, Schneider, & Frank, 2018;Foppolo, Mazzaggio, Panzeri & Surian, 2021;Gotzner, Barner, & Crain, 2020). For example, Horowitz et al showed children three book covers with pictures of animals on each.…”
Section: Priming Enrichment In Childrenmentioning
confidence: 99%